Can Early Programming Performance Predict Computer Science Students’ Success? - Debby Erce Sondakh, S.Kom, M.T, Ph.D; Stenly Richard Pungus (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
Investigating the possibility of lower-level computer programming courses predicting future performance of computer science students has received a lot of attention from scholars. This study mainly aimed to predict the success of computer science students based on their performance in the first two computer programming courses, namely Computer Programming I and Computer Programming II. The study employed a quantitative correlational design. Six years of data from graduating students were analyzed. The results demonstrate that the better the grade on Computer Programming I and II, the shorter the study duration. When further analysis was conducted to find out whether gender diversity exists, the results demonstrated that in Computer Programming I and II, female students outperformed males. Statistically, this difference was only significant in Computer Programming I. A greater proportion of female students graduated on time, yet it is not statistically significant.